2022
DOI: 10.3390/pr10071331
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Reforming of Methane over Nickel-Supported Zeolites: A Screening Study

Abstract: As the utilization of zeolites has become more frequent in the dry reforming of methane (DRM) reaction, more systematic studies are required to evaluate properly the influence of zeolites’ composition and framework type on the performance. Therefore, in this work, a step-by-step study was performed with the aim of analyzing the effects of Ni loading (5, 10 or 15 wt.% over USY(3) zeolite), Si/Al ratio (3, 15 or 38 on USY zeolites with 15 wt.% Ni) and framework type (USY, BEA, ZSM-5 or MOR for 15 wt.% Ni and Si/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Following synthesis, we performed nitrogen adsorption‐desorption isotherms and XRD analysis to verify our assumption (see Figures S19 and S20 in the SI). We opted for these techniques as they serve as indirect methods for assessing the dispersion of a metallic phase over a support [79–86] . In summary, the analysis of the additional tests confirmed that Ni impregnated by the SEA method does not alter the textural and structural properties of the support, unlike the wet impregnation method (see to Appendix K in the SI).…”
Section: Resultsmentioning
confidence: 81%
“…Following synthesis, we performed nitrogen adsorption‐desorption isotherms and XRD analysis to verify our assumption (see Figures S19 and S20 in the SI). We opted for these techniques as they serve as indirect methods for assessing the dispersion of a metallic phase over a support [79–86] . In summary, the analysis of the additional tests confirmed that Ni impregnated by the SEA method does not alter the textural and structural properties of the support, unlike the wet impregnation method (see to Appendix K in the SI).…”
Section: Resultsmentioning
confidence: 81%
“…Also, Rh particle agglomeration was seen for 4 wt % Rh/H-Beta, while the coke formed was only 0.1 and 0.2 wt % for 0.5 and 1 wt % Rh/H-Beta, reflecting that a high loading led to metal aggregation because of the weaker interaction with zeolite support, while a low loading facilitated carbon gasification on the better-dispersed metal particles (Table 2). 155,156 Similarly in Co/zeolite Y, although 10% Co/zeolite Y exhibited a higher initial activity than 5% Co/zeolite Y owing to more active sites, a conversion drop was shown in the stability test, which was a result of the Co sintering and coke deposition in 10% Co/zeolite Y. 121 However, a small metal loading may hinder reactant activation.…”
Section: Metal Loadingmentioning
confidence: 99%
“…Their research delivers a clear message on how the Si/Al ratio in zeolite membranes affects the separation performance; therefore, this approach may be used for the enhancement of CO2 hydrogenation processes. Bacariza and coworkers [30] looked into the influence of Ni loading and Si/Al ratio on the behavior of framework zeolites during the dry reforming of methane (DRM). It was revealed that the ratio of Si/Al influenced tremendously the catalytic activity, which showed outstanding results of low alkalinity and higher reducibility at lower temperatures.…”
Section: Si/al Ratiomentioning
confidence: 99%